Medicinal and therapeutic properties of garlic, garlic essential oil, and garlic-based snack food: An updated review - Verma, Tarun; Aggarwal, Ankur; Dey, Priya; Chauhan, Anil Kumar; Rashid, Summya; Chen, Kow-Tong; Sharma, Rohit (Frontiers in Nutrition, 2023)
Garlic (Allium sativum) is an edible tuber belonging to the family Liliaceae. It has been used since ancient times as a spice to enhance the sensory characteristics of food and as a household remedy for the treatment of a variety of ailments. Garlic has been studied for its medicinal and therapeutic effects in the treatment of various human diseases for a long time. Health benefits associated with the consumption of garlic are attributed to the various sulphur compounds present in it such as allicin, ajoene, vinyl-dithiin, and other volatile organosulfur compounds which are all metabolized from aliin. Several researches in the literature have shown evidence that garlic exhibits antioxidant, antiviral, anti-microbial, anti-fungal, antihypertensive, anti-anemic, anti-hyperlipidemic, anticarcinogenic, antiaggregant, and immunomodulatory properties. The present review identifies and discusses the various health benefits associated with the consumption of garlic, its essential oil, and bioactive constituents, along with exploring the various snack-food products developed by incorporating garlic.